Pengaruh Risiko Kredit, Profitabilitas, dan Likuiditas terhadap Harga Saham pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2022-2025 - Laila Cahya Humair; Hari Setiono; Nur Ainiyah (Indo Publishing, 2026)
The variation in stock prices in the banking sector is caused by the company's fundamental situation and investors' views on financial data. This study aims to examine the impact of credit risk, profitability, and liquidity on stock prices, referring to signaling theory and agency theory. A quantitative method with an associative approach was applied in this study. The population consisted of 47 banks listed on the IDX. Using purposive sampling, 25 banks were selected, resulting in 100 observations from 2022 to 2025. Secondary data were sourced from annual reports and stock price data, with credit risk estimated using NPL, profitability measured through ROE and NIM, liquidity measured with LDR, and stock prices using the closing price three days after the annual report release. The analysis was conducted using multiple linear regression with IBM SPSS 26. The study results show that NPL and LDR don’t affect stock prices, while ROE and NIM have a positive and significant relationship with stock prices. The research model is considered valid, with an Adjusted R² of 55.7%. The findings suggest that investors pay more attention to profitability when analyzing bank stocks.